Design and Implementation of an Omni-Directional Underwater Acoustic Micro-Modem Based on a Low-Power Micro-Controller Unit - Won, Tae-Hee (Molecular Diversity Preservation International (MDPI), 2012)
For decades, underwater acoustic communication has been restricted to the point-to-point long distance applications such as deep sea probes and offshore oil fields. For this reason, previous acoustic modems were typically characterized by high data rates and long working ranges at the expense of large size and high power consumption. Recently, as the need for underwater wireless sensor networks (UWSNs) has increased, the research and development of compact and low-power consuming communication devices has become the focus. From the consideration that the requisites of acoustic modems for UWSNs are low power consumption, omni-directional beam pattern, low cost and so on, in this paper, we design and implement an omni-directional underwater acoustic micro-modem satisfying these requirements. In order to execute fast digital domain signal processing and support flexible interfaces with other peripherals, an ARM Cortex-M3 is embedded in the micro-modem. Also, for the realization of small and omni-directional properties, a spherical transducer having a resonant frequency of 70 kHz and a diameter of 34 mm is utilized for the implementation. Physical layer frame format and symbol structure for efficient packet-based underwater communication systems are also investigated. The developed acoustic micro-modem is verified analytically and experimentally in indoor and outdoor environments in terms of functionality and performance. Since the modem satisfies the requirements for use in UWSNs, it could be deployed in a wide range of applications requiring underwater acoustic communication.